Organised crime: dark sides of globalization - Robertson-von Trotha, Caroline Y.; Flörchinger, Silke (Reihe Kulturwissenschaft interdisziplinär, 2012)
"In the course of globalisation, organised crime has develped into a trnsnational phenomenon that increasingly poses a challenge to naitiona judicial systems and democracies. In the public's perception, however, the relevance of the topic is often understimated...This volume addresses...questions from a sociological, economic, criminological, and judicial perspective, and offers approaches to possible solutions" -- P. [4] of cover